British and German military planning in World War II regarding the ‘long-haul neutrals’ (Vegueta: Anuario de la Facultad de Geografía e Historia, 2025)
The main objective of this study is to compare the military planning of the United Kingdom and the Third Reich regarding Spain and other European neutral countries (Ireland, Portugal, Sweden, Switzerland, and Turkey) throughout each of the phases of the Second World War. This required a systematic compilation of plans from primary sources in The National Archives in the United Kingdom and the Bundesarchiv-Militärarchiv in Germany. The main conclusion is that Spain's non-belligerent position was a key differentiating factor influencing the strategy adopted by each side towards the other European neutral countries.